Physiological Profile of Neuropeptide Y-Expressing Neurons in Bed Nucleus of Stria Terminalis in Mice: State of High Excitability - Walter, Achim Leonhard; Bartsch, Julia Constance; Datunashvili, Maia; Blaesse, Peter; Lange, Maren Denise; Pape, Hans-Christian (Frontiers in Cellular Neuroscience, 2018)
Both, the anterior bed nucleus of the stria terminalis (BNST) and the neuropeptide Y (NPY) system are involved in shaping fear and defensive responses that adapt the organism to potentially life-threatening conditions. NPY is expressed in the BNST but NPY-expressing neurons in this critical hub in the stress response network have not been addressed before. Therefore, we performed whole-cell patch-clamp recordings in acute slices of anterior BNST from Npy-hrGFP transgenic mice to identify and characterize NPY-expressing neurons. We show that NPY-positive and NPY-negative neurons in anterior BNST match the previous classification scheme of type I (Regular Spiking), type II (Low-Threshold Bursting), and type III (fast Inward Rectifying) cells, although the proportion of these physiological phenotypes was similar within both neuronal subpopulations. However, NPY-positive and NPY-negative neurons possessed distinct intrinsic electrophysiological properties. NPY-positive neurons displayed higher input resistance and lower membrane capacitance, corresponding to small cell bodies and shorter less ramified dendrites, as compared to their NPY-negative counterparts. Furthermore, NPY-positive neurons generated higher frequent series of action potentials upon membrane depolarization and displayed significantly lower GABAA receptor-mediated synaptic responsiveness during evoked, spontaneous and elementary synaptic activity. Taken together, these properties indicate an overall state of high excitability in NPY-positive neurons in anterior BNST. In view of the role of the anterior BNST in anxiety- and stress-related behaviors, these findings suggest a scenario where NPY-positive neurons are preferentially active and responsive to afferent inputs, thereby contributing to adaptation of the organism to stressful environmental encounters.